Assessing the viability of soil successive straw biochar amendment based on a five-year column trial with six different soils: Views from crop production, carbon sequestration and net ecosystem economic benefits. (1st September 2019) - Bi, Yucui; Cai, Siyuan; Wang, Yu; Xia, Yongqiu; Zhao, Xu; Wang, Shenqiang; Xing, Guangxi
Abstract: Converting straw to biochar (BC) followed by successive application to soil has been increasingly suggested as a multi-win approach for soil fertility improvement, carbon (C) sequestration and efficient disposal of straw residues in intensive cropping agroecosystems. However, different soil types response differently in terms of crop growth and non-CO2 greenhouse gas (GHG) emissions after BC application. Furthermore, few studies have comprehensively evaluated the net global warming potential (GWP) and net ecosystem economic benefits (NEEB) after long-term BC incorporation across representative soil types in China. A five-year outdoor column experiment was conducted using three rice-wheat rotated paddy soils and three millet-wheat rotated upland soils developed from different parent materials. Rice straw BC application rates of 0, 2.25 and 11.3 Mg ha −1 were used in each crop season with identical doses of NPK fertilizers. Compared with the no BC controls, BC significantly boosted crop growth, enhanced C sequestration, and decreased cumulative N2 O and CH4 emissions in all six soils over five rotation cycles. The response of the upland soils to BC was better in terms of crop growth and N2 O mitigation, whereas the soil organic carbon (SOC) increment and CH4 mitigation were less effective compared with the paddy soils. Net GWP decreased 0.6–19 fold after BC application; however, given the low trade price of CO2 (0.21 × 10 3 CNY Mg −1 ), only a small contribution was made in terms of C costs to the NEEB. The BC-induced NEEB was mainly dependent on grain yield gains and BC costs. These findings highlight that widespread adoption of successive straw BC application to farmland requires an increase in crop yield and substantial lowering of the BC cost regardless of the soil type. From the standpoints of agronomics, environment and economics, acid upland soil shows most potential in terms of BC application. Graphical abstract: Image 1 Highlights: The viability of successive biochar applications to six soils over ten crop seasons was evaluated. Biochar boosted crop growth, slowed GHG emissions and locked away C from six soil-crop systems. The sustainability of straw biochar used depends on grain yield gains and biochar costs. Biochar used in acid and upland soils were more potential compared to alkaline and paddy soils.